CAPTION KONSEP DIRI: STRATEGI PERSONAL BRANDING PADA MEDIA INSTAGRAM - Nashrudin Latif; Ferry Hariawan (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2021)
The purpose of this study is to reveal personal branding strategies through captions of new students' self-concepts on Instagram media. The subjects of this study were freshmen in the first semester, who experienced a transitional period of changing status from student to student. Qualitative research method used with content analysis approach. Data were obtained through written documents, from uploading captions about self-concept, and interviews. Self-concept is defined as a way of looking at oneself. The development of a positive self-concept is the basic ingredient for implementing a personal branding strategy. Personal branding is defined as an individual's effort to market himself to gain positive credibility recognition from others. The results of the study indicate that the caption upload contains a self-concept, includes self-introduction about the current condition, expectations and self-assessment of the advantages and disadvantages that are in accordance with the concept of forming personal branding. Where the self-concept modeling process, assisted by critical assessment, is able to form different choices for the desired personal branding. The practical implication is that the disclosure of the meaning of the self-concept caption with the personal branding point of view is that for individuals it can form a positive image through a digital track record, for other people/society/netizens/followers to perceive individuals correctly and for business people it can be used as a reference for assessing the feasibility of individuals becoming endorsement of products or services offered.